Emergency Physician Performed Ultrasound-Guided Abdominal Paracentesis: A Retrospective Analysis - Brandon Wubben; Jad Dandashi; Omar Rizvi; Srikar Adhikari (CINQUILL Medical Publishers Inc., 2024)
Background: Emergency physicians commonly perform ultrasound-assisted abdominal , using point of care ultrasound (POCUS) to identify and select a site for needle insertion. However, ultrasound-guided has the benefit of real-time needle visualization during the entire procedure. Our objective was to characterize the performance of emergency physician-performed ultrasound-guided using POCUS, their ability to achieve good in-plane needle visualization, and factors associated with procedural success. Methods: A POCUS database was retrospectively reviewed for examinations where abdominal was performed by an emergency physician at two academic urban emergency departments over a six-year period. Medical records were reviewed for demographics, presenting history, complications, and hospital course. Descriptive statistics were used to summarize the data. Results: 131 patients were included in the final analysis. The success rate for ultrasound-guided was 97.7% (84/86, 95% CI 92-100%) compared to 95.6% (43/45, 95% CI 85-99%) for ultrasound-assisted (p = .503). 58% (50/86) demonstrated good in-plane needle visualization; 17% (15/86) had partial or out-of-plane visualization; and 24% (21/86) did not demonstrate needle visibility on their saved POCUS images. All four procedural failures were performed by first- or second-year residents using a transducer, while all procedures using a linear transducer were successful. The most common complications were leak, infection at the site, and minor bleeding. Conclusions: Emergency physicians with training in real-time needle guidance with ultrasound were able to use POCUS to perform ultrasound-guided in the emergency department with a high success rate and no fatal complications. Based on our experience, we recommend performing ultrasound-guided using a linear transducer, with attention to identifying vessels near the procedure site and maintaining sterile technique.